Reaffirming the value of professionalism in public administration: the Ugandan experience - Sezi, Prisca B.M. (1997)
In the pursuit of a professional public service, it is hard to overemphasize the importance of such time-honoured values as accountability, equity, integrity, transparency, neutrality, efficiency and effectiveness. In Uganda, however, standards of professionalism in the public service were greatly eroded as a direct consequence of the political turmoil and economic decline which the country suffered during the 1970s and 1980s. Among the results were poor remuneration and poor working conditions for civil servants - an unhealthy environment for promoting the values of professionalism. The National Resistance Movement (NRM) Government which came to power in 1986 saw the need to revitalize the civil service which had fallen into considerable disarray. In 1989, a Public Service Review and Reorganization Commission was appointed to study the problems of the civil service. The Commission confirmed that civil servants not only lacked the requisite experience and qualifications for their jobs but also lacked effectiveness, integrity and even patriotism. In addition, the Commission identified problems of probity and accountability and substantial corruption. The civil service was declared to be inefficient and employees were found to have low morale
Keywords: Public administration - Uganda; Civil service - Uganda; Civil service